The IEEE 802.17 media access protocol for high-speed metropolitan-area resilient packet rings. - Ping Yuan (IEEE Network : the magazine of global information exchange)
The resilient packet ring (RPR) IEEE 802.17 standards is under development as a new high-speed technology for metropolitan backbone networks. A key performance objective of PRP is to simultaneously achieve high utilization, spatial reuse, and fairness, an objective not achieved by current technologies such as SONET and Gigabit Ethernet or legacy ring technologies, such as FDDI. The core technical challenge for RPR is the design of a fairness algorithm that dynamically throttles traffic to achieve these properties. The difficulty is in the distributed nature of the problem, that upstream ring nodes must inject traffic at a rate according to congestion and fairness criteria downstream. This article provides an overview of the RPR protocol with a focus on medium access and fairness.